THE RESOLUTION OF SOCIAL CONFLICT IN THE NATIONAL CONSTITUTION AND ISLAMIC PERSPECTIVES: Integrating Formal and Non-Formal Approaches - Hanafi, Yusuf; Thoriquttyas, Titis (AL-TAHRIR, 2018)
Abstract: Social conflict resolution is often viewed as a complex matter. Thus, a non-formal approach is needed to complement the formal approach of Law No.7 of 2012 that was legalized by The House of Representatives of the Republic of Indonesia several years ago. It is not uncommon for non-formal conflict resolution to be more effective since it has a broader acceptance in society. A non-formal approach does not mean to undermine the existing laws; it can even complement it and become an alternative solution when the formal approach does not work. This study aims to describe the model of social conflict resolution based on Law No.7 of 2012 and the Quran as a comprehensive combination in resolving social conflict through a formal and non-formal approach. This study discusses that the Quran has a unique formula in resolving social conflicts by emphasizing the principal of kindness to prevent conflicts and implementing justice as a resolution to conflicts.Ø§Ù„Ù…Ù„Ø®Øµ: Ù…Ø¹Ø§Ù„Ø¬Ø© Ø§Ù„Ù†Ù€Ø²Ø§Ø¹ Ø§Ù„Ø§Ø¬ØªÙ…Ø§Ø¹ÙŠ ÙƒØ«ÙŠØ±Ø§ Ù…Ø§ ÙŠÙƒÙˆÙ† Ø£Ù…Ø±Ø§ ØµÙŽØ¹Ù’Ø¨Ø§Ù‹ ØªØ¯ÙˆÙ’Ø±Ù ØÙˆÙ„Ù‡ Ø£Ø¨Ø¹Ø§Ø¯ÙŒ Ù…Ø¹Ù‚Ù‘ÙŽØ¯ÙŽØ©ÙŒ, ÙˆÙ‡Ù†Ø§Ùƒ ØØ§Ø¬Ù‘Ø©ÙŒ Ù…Ø§Ø³Ù‘Ø©ÙŒ Ù„Ù…Ø¹Ø§Ù„Ø¬ØªÙÙ‡ Ù…Ù† Ø§Ù„Ù†Ù‘Ù‡Ø¬ ØºÙŠØ± Ø§Ù„Ø±Ø³Ù…ÙŠÙ‘ Ø¨Ø¬Ø§Ù†Ø¨ Ø§Ù„Ù†Ù‡Ø¬ Ø§Ù„Ø±Ø³Ù…ÙŠÙ‘ Ø§Ù„Ù‘Ø°ÙŠ Ù‚Ø±Ù‘ÙŽØ±ÙŽÙ‡ Ù…Ø¬Ù„Ø³Ù Ø§Ù„Ù†Ù‘ÙˆØ§Ø¨ Ø§Ù„Ø´Ø¹Ø¨ÙŠ Ø¨ÙˆØ§Ø³Ø·Ø© Ø§Ù„Ù‚Ø§Ù†ÙˆÙ† Ø±Ù‚Ù… 7 Ø³Ù†Ø© 2012 Ø¹Ø¯Ø© Ø³Ù†ÙˆØ§Øª Ù…Ø§Ø¶ÙŠØ©, Ø¥Ø°Ù’ Ù‚Ø¯ ÙŠÙƒÙˆÙ† Ø§Ù„Ù†Ù‡Ø¬ ØºÙŠØ± Ø§Ù„Ø±Ø³Ù…ÙŠÙ‘ Ø£ÙƒØ«ÙŽØ±ÙŽ ÙØ¹Ø§Ù„ÙŠØ©Ù‹ ÙˆÙ‚Ø¨ÙˆÙ„Ù‹Ø§ Ù„Ø¯Ù‰ Ø§Ù„Ù…Ø¬ØªÙ…Ø¹ ÙÙŠ Ù…Ø¹Ø§Ù„Ø¬Ø© Ø§Ù„Ù†Ù€Ø²Ø§Ø¹ Ø§Ù„Ø§Ø¬ØªÙ…Ø§Ø¹ÙŠ. ÙˆÙ‡Ø°Ø§ Ø§Ù„Ù†ÙˆØ¹ Ù…Ù† Ø§Ù„Ù†Ù‡Ø¬ Ù„Ø§ ÙŠØ¹Ù†ÙŠ Ø¥Ù„ØºØ§Ø¡ Ø§Ù„Ù‚Ø§Ù†ÙˆÙ† Ø§Ù„ÙˆØ·Ù†ÙŠ Ø§Ù„Ø±Ø³Ù…ÙŠ, Ø¨Ù„ ÙŠØ³ÙØ¯Ù‘ÙÙ‡ ÙˆÙŠÙƒÙ…Ù‘ÙÙ„ÙÙ‡Ù â€”Ø®ØµÙˆØµØ§ Ø¥Ø°Ø§ ÙƒØ§Ù† Ù‡Ù†Ø§Ùƒ Ø¹ÙˆØ§Ø¹ÙÙ‚Ù ØªØ¹ÙˆÙ‚Ù Ø¯ÙˆÙ† Ù†Ø¬Ø§Ø. ØªØ³ØªÙ‡Ù’Ø¯ÙÙÙ Ù‡Ø°Ù‡ Ø§Ù„Ù…Ù‚Ø§Ù„ÙŽØ©Ù Ø¥Ù„Ù‰ ÙˆØµÙ Ø§Ù„Ù†Ù…Ø§Ø°Ø¬ ÙÙŠ Ù…Ø¹Ø§Ù„Ø¬Ø© Ø§Ù„Ù†Ù€Ø²Ø§Ø¹ Ø§Ù„Ø§Ø¬ØªÙ…Ø§Ø¹ÙŠ Ù…Ù† ÙˆØ¬Ù‡Ø© Ù†Ø¸Ø± Ø§Ù„Ù‚Ø§Ù†ÙˆÙ† Ø±Ù‚Ù… 7 Ø³Ù†Ø© 2012 ÙˆÙˆØ¬Ù‡Ø© Ù†Ø¸Ø± Ø§Ù„Ø¥Ø³Ù„Ø§Ù…, Ø±Ø¬Ø§Ø¡Ù‹ Ø§Ù„ØØµÙˆÙ„ Ø¹Ù„Ù‰ Ø§Ù„Ù†Ù…ÙˆØ°Ø¬ Ø§Ù„Ù…Ø«Ø§Ù„ÙŠ Ø§Ù„Ù…ØªÙƒØ§Ù…Ù„ Ù„Ù‡Ø°Ù‡ Ø§Ù„Ù‚Ø¶ÙŠØ©. ØªØµÙ Ù‡Ø°Ù‡ Ø§Ù„Ù…Ù‚Ø§Ù„Ø© Ø£Ù† Ù„Ù„Ù‚Ø±Ø¢Ù† ØµÙŠØºØ© Ø®Ø§ØµØ© Ù…ØªÙ…ÙŠØ²Ø© ÙÙŠ Ù…Ø¹Ø§Ù„Ø¬Ø© Ø§Ù„Ù†Ù€Ø²Ø§Ø¹ Ø§Ù„Ø§Ø¬ØªÙ…Ø§Ø¹ÙŠ, ÙˆÙ‡Ùˆ ØªØ£ÙŠÙŠØ¯ "Ø§Ù„Ù„Ø·Ù Ù„Ù…Ù†Ø¹ Ø§Ù„Ù†Ø²Ø§Ø¹" ÙˆØªØ·Ø¨ÙŠÙ‚ "Ø§Ù„Ø¹Ø¯Ù„ ÙƒØÙ„ Ù„Ù„ØµØ±Ø§Ø¹"Abstrak: Penanganan konflik sosial seringkali berdimensi kompleks. Oleh karena itu, perlu diupayakan penyelesaian konflik dengan pendekatan non-formal, di samping pendekatan formal melalui Undang-Undang Nomor 7 Tahun 2012 yang disahkan oleh Dewan Perwakilan Rakyat (DPR) Republik Indonesia beberapa waktu silam. Tidak jarang, penanganan konflik secara non-formal justru lebih efektif karena mempunyai level keberterimaan yang lebih luas dan tinggi di tengah masyarakat. Pendekatan non-formal ini tidak dimaksudkan untuk mengesampingkan undang-undang yang telah diberlakukan itu, tetapi justru melengkapinya sekaligus menjadi alternatif solusi jika pendekatan formal mengalami kebuntuan. Kajian ini bertujuan untuk mendeskripsikan model penanganan konflik sosial menurut UU Nomor 7 Tahun 2012 dan Al-Qurâ€™an, sebagai kombinasi penanganan konflik sosial yang komprehensif, baik melalui jalur formal maupun non-formal. Tulisan ini akan memaparkan bahwa Al-Qurâ€™an memiliki formula penanganan konflik sosial yang unik dan khas, yakni penekanan prinsip kebaikan sebagai prevensi konflik, dan penerapan prinsip keadilan sebagai resolusi konflik.